FREQUENCY OF SUBCLINICAL HYPO AND HYPERTHYROIDISM IN PATIENTS PRESENTING WITH CONGESTIVE HEART FAILURE - ANUM, H; QURESHI, AE; ULLAH, N; SAJJAD, M; FAROOQ, U; DAR, WA (Biological and Clinical Sciences Research Journal, 2023)
Congestive heart failure is among the most common presentations in Cardiology inpatient and outpatient departments. It is associated with several long- and short-term complications and among these patients hypo and hyperthyroidism is found frequently. This study aims to determine the frequency of subclinical hypo or hyperthyroidism in cases with congestive heart failure. This cross-sectional study was conducted at the Rehmatul-Lol-Alameen institute of cardiology, PESSI, from 23-08-2020 to 22-02-2021. This study included cases of both genders aged 30-70 years suffering from congestive heart failure. Hypothyroidism was labeled when the TSH level was between 4.6 to 10 mIU/L, and hyperthyroidism was labeled when the TSH level was between 0.01 to 0.02 mIU/L. In this study, there were 91 cases of congestive HF. There were 61 (67.03%) males and 30 (32.97%) females. The mean age of the subjects was 2 51.53±9.23 years, and the mean weight was 75.71±15.18 kg. There were 20 (21.98%) cases with a history of DM. Hypothyroidism was observed in 19 (20.88%) of the cases, and hyperthyroidism in 08 (8.79%) of the cases. There was no significant difference in gender, age, BMI, duration of HF, and DM with hypo and hyperthyroidism. We can conclude from the study results that hypo and hyperthyroidism are common in cases with congestive heart failure, though hypothyroidism cases were found to be double than the hyperthyroidism.